Analisis faktor - faktor yang mempengaruhi pengambilan keputusan konsumen terhadap pembelian rumah : Studi kasus di Perumahan Griya Emas Kabupaten Pamekasan - Santoso, Fuji; Anas, Zulviar (Nur Science Institute, 2021)
The increase in population causes an increase in the demand for housing. Many developers use the increasing need for houses to provide housing with various facilities. Various kinds of developer offer make the public as consumers are faced with several factors in the decision to buy a house. The purpose of the study was to determine the effect of price, building design, physical building, facilities, and location and to determine the dominant factors in home-buying decisions. The research method uses quantitative methods. The results showed that the price factor, the building design factor, the physical building factor, the facility factor, and the location factor influenced the decision to buy a house. The most dominant factor in influencing home-buying decisions is the price factor. Other influencing factors are location, building physical, facility, and building design factors.